The protective role of CD73 in periodontitis: preventing hyper-inflammatory fibroblasts and driving osteoclast energy metabolism - Ramos-Junior, Erivan S.; Dawson, Shantiece; Ryan, Weston; Clinebell, Braden; Serrano-Lopez, Rogelio; Russell, Marsha; Brumbaugh, Rylee; Zhong, Roger; Gonçalves Fernandes, Jussara; Shaddox, Luciana M.; Cutler, Christopher W.; Morandini, Ana Carolina (Frontiers in Oral Health, 2023)
Periodontitis is an immune-mediated inflammatory disease affecting almost half of the adult population and is the leading cause of tooth loss in the United States. The role of extracellular nucleotide signaling including nucleotide metabolizing enzyme CD73 adds an important layer of interaction of purine mediators capable of orchestrating inflammatory outcomes. CD73 is able to catabolize 5′-adenosine monophosphate into adenosine at the extracellular level, playing a critical role in regulating many processes under physiological and pathological conditions. Here, we explored the role of CD73 in ligature-induced periodontitis in vivo comparing wild-type C57Bl/6J and CD73-deficient mice. We assessed gingival levels of inflammatory cytokines in vivo and in murine gingival fibroblasts in vitro, as well as bone loss, and RANKL-induced osteoclastogenesis.We have also analyzed CD73 mRNA in samples derived from patients diagnosed with severe periodontitis. Our results in mice show that lack of CD73 resulted in increased inflammatory cytokines and chemokines such as IL-1β, IL-17, Cxcl1 and Cxcl2 in diseased gingiva relative to the healthy-controls and in comparison with the wild type. CD73-deficient gingival fibroblasts also manifested a defective healing response with higher MMP-13 levels. CD73-deficient animals also showed increased osteoclastogenesis in vitro with increased mitochondrial metabolism typified by excessive activation of oxidative phosphorylation, increased mitochondrial membrane potential and accumulation of hydrogen peroxide . Micro-CT analysis revealed that lack of CD73 resulted in decreased bone mineral density, decreased trabecular bone volume and thickness as well as decreased bone volume in long bones. CD73 deficiency also resulted in increased alveolar bone loss in experimental periodontitis. Correlative studies of gingival samples from severe (Grade C) periodontitis showed decreased levels of CD73 compared to healthy controls, further supporting the relevance of our murine results. In conclusion, CD73 appears to play a protective role in the gingival periodontal tissue and bone homeostasis, regulating hyper-inflammatory state of stromal fibroblasts and osteoclast energy metabolism and being an important candidate for future target therapies to prevent or control immune-mediated inflammatory and osteolytic diseases.